Association of BRCA1, BRCA2, RAD51, and HER2 gene polymorphisms with the breast cancer risk in the Bangladeshi population - Parvin, Salma; Islam, Md. Siddiqul; Al-Mamun, Mir Md. Abdullah; Islam, Mohammad Safiqul; Ahmed, Maizbha Uddin; Kabir, Eva Rahman; Hasnat, Abul (© 2016 The Japanese Breast Cancer Society, 2016)
This article was published in Breast Cancer [© 2016 The Japanese Breast Cancer Society] and the definite version is available at: http://link.springer.com/article/10.1007/s12282-016-0692-5